The Herpesvirus Nuclear Egress Complex Component, UL31, Can Be Recruited to Sites of DNA Damage Through Poly-ADP Ribose Binding - Maxwell R. Sherry (Nature Portfolio, 2017)
Abstract The herpes simplex virus (HSV) UL31 gene encodes a conserved member of the herpesvirus nuclear egress complex that not only functions in the egress of DNA containing capsids from the nucleus, but is also required for optimal replication of viral DNA and its packaging into capsids. Here we report that the UL31 protein from HSV-2 can be recruited to sites of DNA damage by sequences found in its N-terminus. The N-terminus of UL31 contains sequences resembling a poly (ADP-ribose) (PAR) binding motif suggesting that PAR interactions might mediate UL31 recruitment to damaged DNA. Whereas PAR polymerase inhibition prevented UL31 recruitment to damaged DNA, inhibition of signaling through the ataxia telangiectasia mutated DNA damage response pathway had no effect. These findings were further supported by experiments demonstrating direct and specific interaction between HSV-2 UL31 and PAR using purified components. This study reveals a previously unrecognized function for UL31 and may suggest that the recognition of PAR by UL31 is coupled to the nuclear egress of herpesvirus capsids, influences viral DNA replication and packaging, or possibly modulates the DNA damage response mounted by virally infected cells.